'Life just kind of sparkles': clients' experiences of being in cognitive behavioural group therapy and its impact on reducing shame in obsessive compulsive disorder. (25th March 2015) - Spragg, Melanie; Cahill, Sharon
Abstract: This study explored the personal accounts of service users relating to their experiences of being in group cognitive behavioural therapy (GCBT) for obsessive compulsive disorder (OCD). Eight participants were purposively selected from two groups whose therapy had finished. These participants were interviewed, the data transcribed verbatim and analysed using interpretative phenomenological analysis (IPA). Five superordinate themes were generated: 'Engagement in the group process', 'Normalizing', 'Courage to fight', 'Being my own therapist' and 'Restricted vs . engagement with life'. The findings in this study have implications for theory in terms of the relevance of shame-based appraisals in conceptualizations of OCD. Suggestions for future groups include the importance of exploring the development of the problem in the group setting and highlight an important role for the group in terms of increasing motivation and preventing dropout. Directions for future research and implications for theory are explored.